Meat and meat by-products carcase study. II. Connective tissue, fat tissue and by-products of carcase - ΠΑΠΑΔΟΠΟΥΛΟΣ, ΧΡΥΣΑΝΘΟΣ TP. (Journal of the Hellenic Veterinary Medical Society, 2019)
Connective tissue, fat tissue and the meat by-products of carcase, were studied from anatomical, histological and chemical point of view. The components of connective tissue are collagen fibers, reticular fibers, elastic fibers, ground substance and several cell variétés. It is well known that muscle cells do not occur in the absence of connective tissue. Fat tissue is consisted from fat cells. The living fat cell is a large, brilliant, spherical body, probably arised from mesenchymale cells, and these undifferentiated cells are most often près ent along small blood vessels. The developing fat cells are usually found scattered in loose connective tissue, especialy near blood vessels. Meat meal, feather meal, blood meal, animal fats, and bone meal are the chief animal byproducts used as feed ingredients. Meat meal is the finely ground dry-rendered residue from mammal tissues exclusive of hair, hoof, hide trimmings, blood meals and others. The meat byproducts are lungs., liver, spleen, kidneys, brain stomach and intestines that are free from their contents. Blood meal is the blood in humid or dried condition. Animal fat is ontained from the tissues of mammals and consists predominantly of glyceride esters of fatty acids.